Fluoroscopic Guidance Increases the Incidence of Thoracic Epidural Catheter Placement Within the Epidural Space: A Randomized Trial. Issue 1 (January 2017) - Parra, Michelle C.; Washburn, Kristin; Brown, Jeremiah R.; Beach, Michael L.; Yeager, Mark P.; Barr, Patricia; Bonham, Kathy; Lamb, Kathryn; Loftus, Randy W.
Abstract : Background and Objectives: Thoracic epidural analgesia can reduce postoperative pain and cardiopulmonary morbidity, but it is associated with a high rate of clinical failure. Up to 50% of clinical failure is thought to be related to technical insertion. In this study, patients undergoing thoracic surgery were randomized to one of two catheter insertion techniques: fluoroscopically guided or conventional loss of resistance with saline/air. Our primary aim was to examine whether fluoroscopic guidance could increase the incidence of correct catheter placement and improve postoperative analgesia. Our secondary aim was to assess the potential impact of correct epidural catheter positioning on length of stay in the postanesthesia care unit and total hospital length of stay. Methods: This randomized clinical trial was conducted at Dartmouth-Hitchcock Medical Center over 25 months (January 2012 to February 2014). Patients (N = 100) undergoing thoracic surgery were randomized to fluoroscopic guidance (n = 47) or to loss of resistance with saline/air (n = 53). Patients were followed for the primary outcomes of 24-hour morphine use, 24-hour numeric pain scores, and the incidence of epidural catheter positioning within the epidural space. Postanesthesia care unit and total hospital lengths of stay were evaluated as secondary outcome measurements and compared for patients with correct epidural catheter positioning and those without correct epidural catheter positioning. Results: One hundred patients were included in an intention-to-treat analysis. Numeric pain scores and 24-hour morphine consumption were no different between groups. Fluoroscopic guidance was associated with an increased incidence of epidural catheter placement within the epidural space compared with loss of resistance with air/saline [fluoroscopic guidance, epidural in 98% (46/47) versus loss of resistance with saline/air, epidural in 74% (39/53)]. There was a significant increase in correct catheter positioning with (odds ratio, 21.07; 95% confidence interval, 2.07-214.38; P = 0.010) or without (odds ratio, 16.15; 95% confidence interval, 2.03-128.47; P = 0.009) adjustment for potentially confounding variables. In an adjusted analysis, correctly positioned thoracic epidural catheters were associated with shorter postanesthesia care unit (5.87 ± 5.39 hours vs 4.30 ± 1.171 hours; P = 0.044) and total hospital length of stay (5.77 ± 4.94 days vs 4.93 ± 2.79 days; P = 0.031). Conclusions: Fluoroscopic guidance increases the incidence of epidural catheter positioning within the epidural space and may reduce postanesthesia care unit and hospital lengths of stay. Future work should validate the effectiveness of this approach. This clinical trial is registered with ClinicalTrials.gov (NCT02678039).